Grammar Challenges In Writing Physics Abstracts: A Student Survey - Izazi, Riandra; Hanif, Raden Mas Muhammad Yassin; Nengsih, Wahyu (Jurnal Pendidikan Bahasa Inggris Proficiency, 2026)
This study aims to identify the grammar problems that undergraduate physics students have when writing research abstracts in English. The study uses a mix of methods with a sequential explanatory design. First, it collects numbers through a survey done with 50 students. Then, it does detailed interviews with two students who were picked for a more in-depth conversation. The findings reveal four primary areas of difficulty: tense and verb-phrase accuracy, complex-sentence construction, article and determiner usage, and prepositional collocation errors. Quantitative results show that students have the most difficulty choosing the correct verb phrase, forming relative clauses, determining articles for abstract scientific concepts, and applying technical collocations. Further analysis showed that these mistakes came from not knowing enough about English grammar rules, translating directly from Indonesian, and not being familiar with how academic writing is done in English. The study found that focusing on teaching English for academic purposes, especially in grammar related to specific subjects and how to write clearly and properly in academic style, is very important for helping physics students write better abstracts.